2009
DOI: 10.1007/s10549-009-0556-1
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer expresses functional NMDA receptors

Abstract: We demonstrate here that functional NMDAR1 receptors and NMDAR2 receptors are expressed by Mcf-7 and SKBR3 breast cancer cell lines, and possibly by most or all high-grade breast tumors, and that these receptors are important for the growth of human breast cancer xenografts in mice. RT-PCR demonstrated mRNA for both NMDAR1 and NMDAR2 receptors are expressed in both Mcf-7 and SKBR3 cell lines, and these messages likely have sequences identical to those reported for human mRNAs. Proteins of the expected respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 22 publications
6
85
0
1
Order By: Relevance
“…Glutamate can also alter cancer cell behavior by modulating ionotropic glutamate receptors, such as the AMPA receptor and NMDA receptors, and metabotropic glutamate receptors (Stepulak et al, 2014; Willard and Koochekpour, 2013). Indeed, a role for the NMDA receptor and metabotropic glutamate receptor-1 in breast cancer has been previously suggested (Mehta et al, 2013; North et al, 2010; Speyer et al, 2012). Secretion of glutamate by glioblastoma cells promotes invasion and tumorigenesis at least partly by causing neuroexcitatory death of surrounding normal brain cells and by activating AMPA receptors (Stepulak et al, 2014; Willard and Koochekpour, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate can also alter cancer cell behavior by modulating ionotropic glutamate receptors, such as the AMPA receptor and NMDA receptors, and metabotropic glutamate receptors (Stepulak et al, 2014; Willard and Koochekpour, 2013). Indeed, a role for the NMDA receptor and metabotropic glutamate receptor-1 in breast cancer has been previously suggested (Mehta et al, 2013; North et al, 2010; Speyer et al, 2012). Secretion of glutamate by glioblastoma cells promotes invasion and tumorigenesis at least partly by causing neuroexcitatory death of surrounding normal brain cells and by activating AMPA receptors (Stepulak et al, 2014; Willard and Koochekpour, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, serum glutamate positively correlates with cancer progression and invasiveness [128], and the protumor effects of glutamate appear to be largely mediated by NMDARs. NMDARs have been identified in a wide variety of tumor types and cancer cell lines (Table 2), and, regardless of subunit configuration, NMDAR blockade reduces both cancer cell proliferation and invasiveness across many different cancers [129][130][131][132][133][134][135][136][137]. While the precise mechanisms underpinning the NMDAR-mediated effects on proliferation are poorly understood, there are clues.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Interestingly, recent report revealed that SKBR3 expressed NMDAR1 and NMDAR2 receptors, both of which are important calcium channels. These receptors are reported to be essential for the growth of human breast cancer xenografts in mice (North et al, 2010). This SKBR3 cell line with high expression of HER2 protein has long been used in various research.…”
Section: Skbr3 Breast Cancer Cell Linementioning
confidence: 99%